Criminal Liability Of Foreign National Children Within Indonesia's Juvenile Justice System Framework - Marantika, I Putu Mega; Sugiartha , I Nyoman Gede; Rideng , I Wayan (Protection: Journal Of Land And Environmental Law, 2026)
This article examines the criminal liability of foreign national children within Indonesia's juvenile justice system, focusing on legal regulation and judicial application in criminal proceedings involving children of foreign nationality. The study addresses the core issue of how Indonesian positive law applies criminal responsibility to foreign national children while ensuring equal legal protection and child-centered justice. The Research employs a normative legal method, drawing on statutory, conceptual, and case approaches, with court decisions as the primary reference for examining judicial practices. The findings reveal that Indonesian law applies the principle of territoriality consistently, allowing foreign national children to be held criminally responsible under the same legal framework as Indonesian children, while prioritizing rehabilitative measures and restorative justice principles. The analysis also demonstrates that judicial authorities emphasize child protection, proportional sanctions, and the best interests of the child in sentencing decisions involving foreign national children. These findings indicate that the juvenile justice system in Indonesia has accommodated foreign national children as legal subjects without discrimination based on nationality. The study concludes that although the existing legal framework sufficiently supports equal treatment and child protection, further institutional coordination and policy refinement are necessary to strengthen rehabilitation-oriented justice for foreign national children within the juvenile justice system